Management of a Garré Sclerosing Osteomyelitis of Forearm: Report of a Resistant Case - Reza Shahryar Kamrani; Hossein Azaditalab; Hesam Alitaleshi; Mohammad Reza Abbaszadeh (Journal of Orthopedic and Spine Trauma)
In 1893 chronic sclerosing osteomyelitis was explained by carle Garre, that characterized by sclerosing and thickening of cortices of bone and obliteration of medullary canal. [01]